2014
DOI: 10.3389/fcell.2014.00035
|View full text |Cite
|
Sign up to set email alerts
|

The prion protein family: a view from the placenta

Abstract: Based on its developmental pattern of expression, early studies suggested the implication of the mammalian Prion protein PrP, a glycosylphosphatidylinositol-anchored ubiquitously expressed and evolutionary conserved glycoprotein encoded by the Prnp gene, in early embryogenesis. However, gene invalidation in several species did not result in obvious developmental abnormalities and it was only recently that it was associated in mice with intra-uterine growth retardation and placental dysfunction. A proposed expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 115 publications
1
12
0
1
Order By: Relevance
“…The seemingly arbitrary PrP CWD distribution pattern in elk fetuses may be more closely related to PrP C expression subtleties, including timing of PrP C expression during normal developmental biology (Peralta et al, 2012), rather than to the dynamics of prion infection and dissemination as seen in adults. As the fetus may be exposed throughout gestation to maternal influx of prions via blood, placental transport or recycling of amniotic fluid (Wooding et al, 1997), and because PrP C isoforms expressed on most fetal cells (Peralta et al, 2012) can serve as docking or conversion scaffolds for prions (Makzhami et al, 2014), it is possible for PrP CWD to be found on virtually any tissue once the fetal-maternal barrier is crossed. Whether these prions had the potential to replicate efficiently in the fetal tissues cannot be ascertained nor whether they would have led to clinical disease at any time post-birth.…”
Section: Discussionmentioning
confidence: 99%
“…The seemingly arbitrary PrP CWD distribution pattern in elk fetuses may be more closely related to PrP C expression subtleties, including timing of PrP C expression during normal developmental biology (Peralta et al, 2012), rather than to the dynamics of prion infection and dissemination as seen in adults. As the fetus may be exposed throughout gestation to maternal influx of prions via blood, placental transport or recycling of amniotic fluid (Wooding et al, 1997), and because PrP C isoforms expressed on most fetal cells (Peralta et al, 2012) can serve as docking or conversion scaffolds for prions (Makzhami et al, 2014), it is possible for PrP CWD to be found on virtually any tissue once the fetal-maternal barrier is crossed. Whether these prions had the potential to replicate efficiently in the fetal tissues cannot be ascertained nor whether they would have led to clinical disease at any time post-birth.…”
Section: Discussionmentioning
confidence: 99%
“…These include the activin receptor-like kinase-2 (ALK2) ( 146 ), whose deficiency leads to developmental arrest at the gastrulation stage ( 147 ). Another possibility to be considered is the binding of STI1 to the PrP C homolog Shadoo, which is abundantly expressed in extra-embryonic annexes, and which may have overlapping functions with PrP C during early development ( 148 ). Notwithstanding, because PrP C is abundant in extra-embryonic annexes ( 148 ), STI1–PrP C protective signaling is likely to also occur in placenta, another important site of immune privilege.…”
Section: Prp C In Cytoprotective and Immunoregulatmentioning
confidence: 99%
“…Therefore, further studies on reproductive tissues are required to resolve the apparent discrepancy in the data. The topic of Sho is also discussed in detail in a review article in this research topic (Makzhami et al, 2014 ). As mentioned above, analysis of the phenotypes of knockout mice and comparison of PrP family members does not fully elucidate the functions of PrP.…”
Section: Prp Family Proteins and Their Knockout Micementioning
confidence: 99%
“…Establishment of more Prnp −/− cell lines will further contribute to our understanding of PrP C function. For example, PrP family members are known to be expressed in reproductive tissues, such as testis, ovary, and placenta (Bonnet and Pailhoux, 2014 ; Makzhami et al, 2014 ). Thus, cells derived from reproductive tissues should also be used for the establishment of Prnp −/− cell lines.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%